Mental Health Peer Navigators: Working With Criminal Justice–Involved Populations - Portillo, Shannon (The prison journal, 2017)
Although peer navigators have gained traction within health care, they are still a relatively new feature of criminal justice-involved organizations. Based on data gathered from interviews, nonparticipant observations, and focus groups from a nonprofit that employs peer navigators to assist clients returning from prison with diagnosed mental illnesses, we argue that peer navigators play multiple roles that extend beyond the client level by influencing the organization and its interaction with the community. Importantly, we discuss these implications for the organization and suggest structure and socialization issues for the integration of criminal justice-involved peer navigators.